(untitled) (Comunicação & Inovação, 2015)
This article makes a systematic analysis of theaudience drop of Jornal Nacional, the mainnews program of Brazilian television. From thestatistical analysis and empirical investigationof the audience ratings between 2000 and 2013,the article quantifies the audience drop as beingof 33.5%, makes comparisons with other channels,whose audiences also dropped, analyzespatterns of variation and presents projectionsfor the audience in the next 14 years. Lastly,it proposes hypotheses for the impact on newscast,which currently face identity and credibilitycrises.